Teetl'it Gwich'in elder interview transcripts and harvester survey data about Porcupine caribou harvesting, harvesting practices, and perceptions of Porcupine caribou population and health, Fort McPherson, NWT, 2007-2008 - Cindy Dickson, Council Of Yukon First Nations; Kristine Wray, Department Of Resource Economics; Brenda Parlee, Department Of Resource Economics; Gwich'in Renewable Resource Board; Gwich'in Social And Cultural Institute; Tetlit Gwich'in Renewable Resource Council (Canadian Cryospheric Information Network, 2016)
Elders data set consisting of digital audio files and transcripts of interviews wth elders. Harvesters data set consisting of written surveys, and digital audio files and transcripts of interviews with harvesters. : Purpose: Data collected to understand local rules-in-use related to caribou harvesting, current practices of active hunters as compared to practices of the elder generation, harvester understandings of population change, health, and migration of the Porcupine caribou. Data collected to understand and contribute to Aboriginal participation in caribou management. : Summary: The data set consists of Tetlit Gwich'in traditional knowledge about caribou. Specifically about what harvesters and elders know about Porcupine caribou health, population change, migration route change, and what is ok to do and not do when harvesting caribou.